Old Wine in a New Bottle - Imam Koeswahyono; Syahriza Alkohir Anggoro; Muhammad Dahlan (University of Jember, 2022)
Resistance to neoliberal legal reforms has increased globally in recent decades due to the failure of water privatization to ensure affordable and sustainable water access in the global South. Referring to the 2004 and 2019 Water Resources Laws, this paper explores how, in the case of Indonesia, the law reproduces and normalizes neoliberal ideologies that frame water as an economic commodity. We argue that Indonesia's current legal regime governing water resources is based on populist rhetoric of fulfilling the human right to water through state management. However, the adopted water governance regime aims to facilitate the establishment of a climate conducive to private sector investment by shifting responsibility for the fulfillment of the human right to water from the state to a market-based allocation system. This paper examines the strategy adopted by the government in securing the water privatization agenda when dealing with judicial activism that requires water to be managed as a public good.